Patterns of Spinal Fusion after Anterior Cervical Discectomy and Fusion with Polyether Ether Ketone Cage Filled Hydroxyapatite - Hesham R Habba (Egyptian Spine Association, 2019)
Background Data: ACDF is one of the most commonly performed operations for degenerative spinal diseases. Traditionally, graft was harvested from iliac crest which was associated with donor site morbidity. This has led to the introduction of many synthetic implants such as PEEK cages to overcome this problem. Purpose: To evaluate the patterns of spinal fusion after ACDF with PEEK cage filled with HA. Study Design: Retrospective clinical study. Patients and Methods: Twenty-five patients that underwent ACDF with PEEK cage filled HA were enrolled in this study through the period from January to December 2017. All patients were submitted to pre- and postoperative clinical and radiological follow-up. Postoperative full neurological and images evaluations were done by independent observer on outpatients at 1, 2, 3, 6, and 12 months. Postoperative neck pain was evaluated using VAS. Radiological evaluation was done using cervical X-ray and images were evaluated using software SurgimapTM. Results: The mean age of our patients was 44.4±6.57 with 9 patients being males and 16 patients females. Total numbers of levels reported were 33 in 25 patients, with 17 patients (68%) undergoing single-level ACDF and 8 patients (32%) double-level ACDF. Five patients (20%) suffered from myeloradiculopathy and twenty patients (80%) had radiculopathy. The mean follow-up was 11.04±1.2. The mean preoperative neck pain VAS was 7.8±1.9, while postoperative VAS was 2.9±1.8. Continuous bridging bony trabeculae were reported in 29 levels (87.9 %) (N=21), while they were absent in 4 levels (12.1%) (N=4). Cage migration was reported in two patients (6%) and both showed >2 mm mobility in dynamic cervical X-ray indicating instability and nonunion. Conclusion: ACDF with PEEK cage filled with HA is a safe and effective method to achieve interbody fusion in patients with cervical disc disease. Although fusion occurred within usual time, remodeling took longer time than that previously reported with iliac graft (2018ESJ171).